KAJIAN PENGGUNAAN LAPIS PONDASI AGREGAT YANG DISTABILISASI SEMEN - Nono Nono (Jurnal Jalan-Jembatan, 2009)
Roads have a strategic role in social, economic, cultural area and National defence and security. However, to provide an adequate performance of pavements as expected by road users is hard to be achieved. One of the problems is caused by inaccurate use of base and sub-base materials. The paper discusses the use of aggregate base and sub-base that stabilized by cement. Based on analysis result, shown that the use of cement-treated base has several advantages, namely, high layer coefficient which can increase service life and more economical. Another advantage is to decrease the use of new aggregate and environmental impact.. Key words: base and sub-base, aggregate, cement stabilized, early damage, cement treated base